If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 24 = 96 Reorder the terms: 24 + 12x = 96 Solving 24 + 12x = 96 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 12x = 96 + -24 Combine like terms: 24 + -24 = 0 0 + 12x = 96 + -24 12x = 96 + -24 Combine like terms: 96 + -24 = 72 12x = 72 Divide each side by '12'. x = 6 Simplifying x = 6
| p(x)=x^2+2x-1 | | 2x+y=2w | | 9r+6r=-31 | | 18x^2-84x+90=0 | | 30=5+0.1x | | 2-6x=-7x+9 | | 3tan(x+0.2)=-2 | | 63-2w^2+4w=0 | | 18=b+a | | 9j-13=68 | | 10x+6=4x-20 | | 3x^2+(6)x+3=0 | | 18x^2-84+90=0 | | 3x^2+(7)x+3=0 | | 39q=5 | | 2ln(3x)=19 | | -6(4x-5)=78 | | 11x-101=108 | | -4(5x-2y+6)= | | 19x^2+4-[8(x^2-3)+6]= | | 4r+7-4r+5= | | 5-2t=1 | | m-7m-6m-7= | | x-4=5x-30 | | 14x+36=106 | | 3(4w+2)= | | 2.5(n+2)=8+0.5n | | -4=-40 | | -2x+4-6x+5=13 | | -3x+8y=9 | | 21=3x+6+10x+4 | | (4x-15)=3x |